Planting Family Medicinal Plants (TOGA) to Enhance the Immune System of the Lojejer Village Community - Syarifah, Hidayatus; Fortuna Sukiran Putri, Evi; Fatmah Rahmawati, Olga; Wulandari, Fitri; Hariyana, Nanik (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This project aims to improve public health in Lojejer Village by promoting the cultivation of Family Medicinal Plants (TOGA). Despite rich natural resources, the community lacks knowledge and skills in TOGA cultivation and use. Method: This project aims to improve public health in Lojejer Village by promoting the cultivation of Family Medicinal Plants (TOGA). Despite rich natural resources, the community lacks knowledge and skills in TOGA cultivation and use. Practical Application: The initiative enhances self-sufficiency in healthcare, reduces reliance on pharmaceuticals, and supports environmental sustainability through TOGA cultivation. Conclusion: The project successfully increased community awareness and proficiency in TOGA cultivation. As a result, it contributed to improved public health and environmental preservation. The initiative underscores the importance of utilizing local natural resources for sustainable health solutions and highlights the role of education in empowering communities.